Understanding the impacts of anthropogenic sound on beaked whales - Cox, T. M.; Ragen, T. J.; Read, A. J.; Vos, E.; Baird, R. W.; Balcomb, K.; Barlow, J.; Caldwell, J.; Cranford, T.; Crum, L.; D'Amico, A.; D'Spain, G.; et al. (J. Cetacean Res. Manage., 2023)
This review considers the effect of anthropogenic sound on beaked whales2. Two major conclusions are presented: (1) gas-bubble disease, induced in supersaturated tissue by a behavioural response to acoustic exposure, is a plausible pathologic mechanism for the morbidity and mortality seen in cetaceans associated with sonar exposure and merits further investigation; and (2) current monitoring and mitigation methods for beaked whales are ineffective for detecting these animals and protecting them from adverse sound exposure. In addition, four major research priorities, needed to address information gaps on the impacts of sound on beaked whales, are identified: (1) controlled exposure experiments to assess beaked whale responses to known sound stimuli; (2) investigation of physiology, anatomy, pathobiology and behaviour of beaked whales; (3) assessment of baseline diving behaviour and physiology of beaked whales; and (4) a retrospective review of beaked whale strandings.